2011
DOI: 10.5536/kjps.2011.38.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Raising Periods on Physico-Chemical Meat Properties of Chicken

Abstract: This study was conducted to investigate the effect of different raising days (30, 36, 42) on physico-chemical meat quality properties of chicken breasts and legs stard with 1 day old. In chemical compositions, moisture and protein contents (%) were decreased whereas fat contents (%) were increased as the raising days. In mineral contents, there was not significantly different in calcium contents. However, there was a decrease of potassium contents (p<0.05) as raising periods increased. Nucleotide-related comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The trays were placed inside the oven until the sample core temperature reached 75°C. Samples were cooled at room temperature; re-weighed and cooking loss was calculated as the difference between the initial and the final sample weights ( Chae et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…The trays were placed inside the oven until the sample core temperature reached 75°C. Samples were cooled at room temperature; re-weighed and cooking loss was calculated as the difference between the initial and the final sample weights ( Chae et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Nasr and Kheiri [ 3 ] reported that the carcass weight according to slaughter age was 1.0 kg and 1.6 kg at 28 and 35 days, respectively. And it was provided by Chae et al [ 4 ], chickens slaughtered at day 30 weighing at least 1.2 kg were not adequate to meet the demand for retail cuts only from domestic broilers at the time in Korea. This study demonstrated that periodic analyses of broiler growth capability are necessary as the broiler productivity indicators continuously improve in the poultry industry.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of raising periods on the carcass characteristics and physio-chemical properties of retail cuts have been previously analyzed in Korean-produced broilers [ 4 , 8 ]. However, it is necessary to increase broiler retail cut use by periodically analyzing the carcass characteristics and retail cut quality according to the typical market days as broiler productivity indicators continue to improve.…”
Section: Introductionmentioning
confidence: 99%
“…Among the poultry meats, duck meat is a healthy food as reported in references such as Donguibogam and Bonchogangmok (Chae et al, 2006). Different from chicken, the color of duck breast meat is red, so it has similar sensory characteristics to beef (Kang et al, 2006a).…”
Section: Introductionmentioning
confidence: 97%